Pengaruh Corporate Image terhadap Customer Loyalty Pertamina dengan Customer Satisfaction sebagai Variabel Mediasi Pada Bensin Pertamax - Febri Suryani; Ratih Mukti Azhar (POLITEKNIK LP3I, 2026)
Issues related to PT Pertamina (Persero)’s reputation and public perception have raised concerns regarding customer loyalty toward Pertamax fuel products. Maintaining customer loyalty has become increasingly important amid growing competition in the fuel industry and public scrutiny of corporate credibility. Therefore, this study aims to analyze the influence of corporate image on customer loyalty, with customer satisfaction acting as a mediating variable among RON 92 gasoline (Pertamax) customers in Surabaya. This research employs a quantitative approach using purposive sampling techniques involving 100 respondents who are active Pertamax users in Surabaya. Data were collected through questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that corporate image has a positive and significant effect on both customer loyalty and customer satisfaction. In addition, customer satisfaction positively and significantly affects customer loyalty. The study also confirms that customer satisfaction mediates the relationship between corporate image and customer loyalty. These findings suggest that strengthening corporate image and improving customer satisfaction are essential strategies for enhancing customer loyalty toward Pertamax products.